General guidelines for operational plan (part 1) - Kamaludin, Mohd Ariff; Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila; Jasni, Nurul Syuhada (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
Before preparing a business plan, it is deemed important to understand the objective, significance and practicality of the operation plan. Inability to prepare a comprehensive operation plan will affect the efficiency of the proposed business. Below is a recommended checklist table (with example) for the operation plan. The table is referring to the operations process of a bakery shop that produces cake.